Mergers and acquisitions: Evidence on post-announcement performance from CEE stock markets - Zaremba, Adam; Płotnicki, Michał (Journal of Business Economics and Management, 2016)
The paper re-examines the short-term and long-term performance following announcements of mergers and acquisitions. This is the first study that comprehensively explores this phenomenon in Central and Eastern European countries. We find strong evidence that announcement of a takeover creates value for both bidders and acquirers in the short run. Simultaneously, contrary to the stylized fact reported by a majority of U.S. based studies, after controlling for local value, size, and momentum factors the mergers and acquisitions do not destroy the value of the acquirers in the long term. The observations are important for corporate governance and portfolio management. The research is based on 109 deals in years 2001–2014. For the short-horizon event studies, we calculate average cumulative abnormal returns and we employ of the zero, index, and market models. For the long-run studies, we build equally and capitalization-weighted calendar-time portfolios and test their performances with CAPM, three-factor and four-factor models.